2023
DOI: 10.3390/rs15041070
|View full text |Cite
|
Sign up to set email alerts
|

Lidar Profiling of Aerosol Vertical Distribution in the Urbanized French Alpine Valley of Annecy and Impact of a Saharan Dust Transport Event

Abstract: The vertical aerosol layering of the troposphere is poorly documented in mountainous regions, particularly in the Alpine valleys, which are influenced by valley and mountain winds. To improve our knowledge of particulate matter trapped in the Annecy valley, synergetic measurements performed by a ground-based meteorological Raman lidar and a Rayleigh-Mie lidar aboard an ultralight aircraft were implemented as part of the Lacustrine-Water vApor Isotope inVentory Experiment (L-WAIVE) over Lake Annecy. These obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Lidar have been used previously to detect the presence of aerosols, although most studies show their use for tracking ambient particulate matter for air-quality studies. For example, in the French Alps ground-based Raman lidar and aircraft lidar were used to sample aerosol, water vapor and temperature profiles in an area subject to valley and mountain winds (Chazette and Totems, 2023). While ground-based Raman lidar allowed the Frontiers in Earth Science frontiersin.org study of the vertical distribution of aerosols, we showed during METEX21 that ground-based Doppler scanning lidar can also provide information about aerosol concentration in the 2d.…”
Section: Discussionmentioning
confidence: 98%
“…Lidar have been used previously to detect the presence of aerosols, although most studies show their use for tracking ambient particulate matter for air-quality studies. For example, in the French Alps ground-based Raman lidar and aircraft lidar were used to sample aerosol, water vapor and temperature profiles in an area subject to valley and mountain winds (Chazette and Totems, 2023). While ground-based Raman lidar allowed the Frontiers in Earth Science frontiersin.org study of the vertical distribution of aerosols, we showed during METEX21 that ground-based Doppler scanning lidar can also provide information about aerosol concentration in the 2d.…”
Section: Discussionmentioning
confidence: 98%
“…One of the methods that currently allow monitoring the aerosol pollution is the lidar method (Chazette 2023;Ma 2019). Lidar systems are an effective method for tracking the transport of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%